The mortality trends of falls among the elderly adults in the mainland of China, 2013-2020: A population-based study through the National Disease Surveillance Points system - Kaiting Zhang; Jinlei Qi; Peijun Zuo; Peng Yin; Yunning Liu; Jiangmei Liu; Lijun Wang; Liping Li (Elsevier, 2022)
Summary: Background: Fall in elderly is a major public health problem. Characterizing trends in fall mortality in different subpopulations could help identifying the needs and developing preventive program for target groups. Here we evaluated the trends of fall-related deaths in Chinese mainland among adults aged ≥60 years specific in sex, age, and provinces, to measure the change in this mortality rate between 2013 and 2020, and to explore the underlying factors influencing this change. Methods: Mortality data were retrieved from the National Disease Surveillance Points system(DSPs) of China, a national-level and provincial-level representative data source, to estimate the impact of elderly falls on mortality in the mainland of China and the specific provinces from 2013 to 2020. The joinpoint regression model was used to estimate the temporal trend of mortality in elderly fallen by calculating the annual percentage change (APC). Findings: The age-standardized falls mortality was 10·438 per 100 000 in 2020. The age-standardized mortality of elderly falls in total and female showed a steady increasing trend (APC=1·96%, p = 0·023 total; APC=3·42%, p = 0·003 female), with it was stable in males (APC=1.26%, p>0·05). Fall mortality among the elderly was more common in people over 70 years of age and increased sharply. The death rates and APCs were highest among the oldest age groups(aged≥85 years). The higher fall mortality was mainly focused in the southeast and central regions, and lower rates were in the northeast provinces and Tibet. Interpretation: Since 2013, the overall fall-related mortality trend among individuals aged ≥60 years has been consistently increasing in China, making it most critical public health challenge. Adherence interventions and increased social support for those at most risk should be considered. Funding: None.